I can learn the Bible : the Joshua code for kids : 52 scriptures every kid should know - Shivers, Holly Hawkins; Hawkins, O. S. (Nashville, TN : Tommy Nelson, a division of Thomas Nelson Publishers, 2014)
"Memory verses and devotions that will write God's word on your children's hearts. In this 52-week devotional for children, author Holly Hawkins Shivers adapts the gift book The Joshua Code (written by her father, O.S. Hawkins) into a devotional that will help kids learn and live the scriptures. Using kid-friendly language, I Can Learn the Bible teaches scriptures in a way children can understand. Each week, kids will commit a new scripture to memory by reading a fun, engaging devotional that's doable for a child."--
Ages 4-8.
Description based on print version record and CIP data provided by publisher.
Keywords: Devotional literature -- Juvenile literature; Children -- Prayers and devotions; Devotional calendars -- Juvenile literature; Christian life -- Juvenile literature; Literature; Devotional literature; Prayers